The Use of Passive and Active Subtitles in Foreign Language Teaching: A View to their Teaching Potential - Torralba-Miralles, Gloria (Íkala, Revista de Lenguaje y Cultura, 2020)
After years of rejection and criticism blaming on their entertaining nature as a source of distraction within the classroom, in recent decades audiovisual translation has been accepted as a tool for language learning. Real-life needs have shown that watching subtitled audiovisual materials enhances language acquisition and foster varied skills, so that it has gained a place in the classroom. Recently, one step forward has been taken in the use of this resource, moving from passive subtitles to active subtitling, in order to turn the target receiver —the foreign-language student— into a subtitler. The present article reviews the didactic possibilities of both activities, analyses the benefits of active subtitling, and presents some subtitling programmes whose features make them feasible for use as a teaching tool.